Stage-Specific Pathological Features of Chronic Kidney Disease: An Article Review - Intan Indriani; Wely Dwi Nopriansyah; Januar Ishak Hutasoit; M. Ikram Zakaria (CV. Inara, 2025)
Chronic Kidney Disease (CKD) is a major global health challenge, with increasing prevalence, particularly in developing countries. CKD is characterized by a gradual and irreversible decline in kidney function, often progressing to End-Stage Renal Disease (ESRD). The pathophysiology of CKD involves structural and functional deterioration in various renal compartments, including the glomerulus, tubules, interstitial tissue, and blood vessels. Histopathological changes play a critical role in disease progression, with interstitial fibrosis, glomerulosclerosis, and tubular atrophy being the hallmark lesions observed across different CKD stages. This review highlights the anatomical pathology of CKD at various stages, focusing on histopathological changes, diagnostic techniques, and factors influencing disease progression. Renal biopsy remains the gold standard for assessing kidney damage, utilizing special stains such as Periodic Acid-Schiff (PAS) to identify fibrosis and sclerosis. However, noninvasive biomarkers like Neutrophil Gelatinase-Associated Lipocalin (NGAL) and Kidney Injury Molecule-1 (KIM-1) have emerged as promising tools for early detection. Studies indicate that histopathologic findings, including interstitial fibrosis and glomerulosclerosis, often correlate with CKD progression more accurately than estimated glomerular filtration rate (eGFR) alone. This review underscores the need for integrating histopathological, clinical, and molecular biomarkers to improve CKD diagnosis and management. A better understanding of kidney pathology can facilitate early detection, refine prognostic assessments, and enhance treatment strategies. Future research should focus on noninvasive diagnostic alternatives and novel therapeutic targets to slow CKD progression and mitigate its global health burden.